The relationship between school culture and school quality: The mediating role of teacher integrity - Muhammad Zidan Nur Ihsan; Bambang Sumardjoko; Furqan Mawardi; Syahril Syahril; Istanto Istanto; Sahensyah Luthfi (Kuras Institute, 2026)
Purpose – Post-pandemic evidence indicates a decline in educational quality across many developing countries. Reports from the Programme for International Student Assessment (PISA) and the Indonesian Ministry of Education have documented learning losses and quality deterioration following Covid-19. While previous studies have identified school culture as an important determinant of school quality, limited attention has been given to the behavioral mechanisms through which this influence operates. This study examines the relationship between school culture and school quality, with teacher integrity as a mediating variable.Method – A quantitative research design was employed using Structural Equation Modeling (SEM). Data were collected from 232 teachers of Muhammadiyah junior high schools in the Solo Raya region, Indonesia, through purposive sampling.Findings – The results revealed that school culture significantly influenced teacher integrity (β = 0.621, p < 0.001), and teacher integrity significantly influenced school quality (β = 0.830, p < 0.001). However, the direct effect of school culture on school quality was not significant (β = 0.055, p = 0.316). Teacher integrity fully mediated the relationship between school culture and school quality (β = 0.516, p < 0.001), indicating that the effectiveness of school culture in enhancing institutional quality depends on the extent to which organizational values are translated into teachers’ ethical and professional conduct.